Unimprovable estimates for solutions of a mixed problem for linear elliptic equations of the second order in a neighborhood of an angular point - Chernetskii, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
Under the minimal conditions for the smoothness of the coefficients of an equation, unimprovable estimates are obtained for solutions of a mixed problem for linear nondivergent elliptic equations of the second order in a neighborhood of an angular point of the boundary of a domain.